The health burden of unhealthy homes in New Zealand: a call for more action and a change in perspective - Gabrielle Ou (New Zealand Medical Student Journal)
The housing crisis in New Zealand poses severe health risks, particularly for children and vulnerable populations. Approximately 20% of homes are damp, cold, or mouldy, contributing to respiratory problems and hospitalisations. The condition of rental properties, often poorer than that of owner-occupied homes, disproportionately affects lower-income and Maori households. The Healthy Homes Standards aim to improve living conditions by setting minimum requirements for heating, insulation, ventilation, moisture control, and draught stopping. However, the reliance on landlord self-certification has limited effectiveness, placing the burden on tenants to report non-compliance. The principle of landlord reported compliance continues the narrative of placing inequitable burden on vulnerable communities, leading to a cycle of health disparities. This viewpoint piece highlights the need for a formal external certification process to ensure consistent adherence to standards. Establishing an agency to certify rental homes and creating a registry would enhance transparency and accountability. A collaborative approach involving landlords, tenants, property managers, community groups, and health advocates is crucial for sustainable solutions. Prioritising tenant well-being and equitable living standards is essential to protect New Zealanders from the dangers of unhealthy homes.